(3GdcQe hGdLhO hGdSNGA (B/s - (3MdHj, SejQ MSjfs ((3WfWG (B- (3eUQ (B:s (3OGQ GdUMGHI ddJQGK,s, 1988)
(3jJMOK Yf GdcQe aj GdbQBf hGdeLJeY GdYQHj GdbOje haj GdESdGe hCSHGH GdcQe hOhGYjg hEGcQGe GdVja hGdLGQ hPj GdbQHj(B.s
Keywords: (3GdCNdGb GdESdGejIs; (3GdcQe (B((3CNdGb ESdGejI(B)s